Pertimbangan Hakim dalam Putusan Wanprestasi di Pengadilan Batang - Khairunas Muhammad Prihartika; Khasanah, Karimatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to analyze the reasons why the Batang Religious Court Judge accepted the default lawsuit case filed by KSPPS Minna Lana Pekalongan and the basis for the Judge's considerations in resolving the default lawsuit case with the usual procedure. This research method uses a juridical-empirical approach with a case study approach and a statutory approach. Both approaches are used to interpret, explore, or gain a deeper understanding. The results of this study indicate that the reason the Batang Religious Court Judge accepted the default lawsuit case filed by KSSPS Minna Lana Pekalongan was based on the suitability of the defendant's residence, namely in Batang Regency. The basis for the Judge's consideration in resolving the default lawsuit with the usual procedure rather than with a simple procedure is because the case contains land rights objects, and the domiciles of the parties are different. So that these 2 things are not categorized or excluded from the provisions of Supreme Court Regulation 4 of 2019 concerning Procedures for Settling Simple Lawsuits, but follow customary customs. This research contributes to the development of the theory and practice of Islamic economic law in the settlement of modern civil disputes, especially in the Religious Court environment. In addition, this research can be an evaluative reference for law enforcement practices in Religious Courts, namely regarding the suitability of judges' considerations to the principles of justice, legal certainty, and benefit.